2017
DOI: 10.1002/adma.201703063
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Molecular Doping in Organic Semiconductors

Abstract: The field of organic electronics thrives on the hope of enabling low-cost, solution-processed electronic devices with mechanical, optoelectronic, and chemical properties not available from inorganic semiconductors. A key to the success of these aspirations is the ability to controllably dope organic semiconductors with high spatial resolution. Here, recent progress in molecular doping of organic semiconductors is summarized, with an emphasis on solution-processed p-type doped polymeric semiconductors. Highligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
573
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(613 citation statements)
references
References 315 publications
9
573
1
4
Order By: Relevance
“…p-type doping of poly(3-hexylthiophene) (P3HT) with 2,3,5,6-tetrauoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ) is a widely used model system (Fig. 1), [7][8][9] where an electron is donated from the highest occupied molecular orbital (HOMO) of P3HT to the lowest unoccupied molecular orbital (LUMO) of F4TCNQ, leading to integer charge transfer.…”
mentioning
confidence: 99%
“…p-type doping of poly(3-hexylthiophene) (P3HT) with 2,3,5,6-tetrauoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ) is a widely used model system (Fig. 1), [7][8][9] where an electron is donated from the highest occupied molecular orbital (HOMO) of P3HT to the lowest unoccupied molecular orbital (LUMO) of F4TCNQ, leading to integer charge transfer.…”
mentioning
confidence: 99%
“…[26,29] Here, the DA complex single crystal is the extreme situation of this doping process. Formation of DA complexes has been wide accepted for explaining the low doping efficiency of organic semiconductors.…”
Section: Doi: 101002/advs201902456mentioning
confidence: 99%
“…Similarly, obvious morphology change was also observed in films on the unmodified SiO 2 /Si substrate ( Figure S8, Supporting Information). [13,48] It should be stressed that the insertion of dopant does not disrupt the molecular packing of the host semiconductor. Figure 5a showed that the pristine film had no diffraction peak, suggesting its random molecular orientation and also well illustrating the low mobility of the undoped device.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…Namely, the LUMO of p-dopants is always close to or deeper than the HOMO of host matrix to fulfill the efficient charge transfer. [13,18] The weak charge transfer has been proven to be formed at the interfaces of donor/acceptor mixtures in OPVs and is believed to be benefit for the device performance. F 4 TCNQ can dope poly(3-hexylthiophene) (P3HT) through an integer charge transfer to form ion pairs, [23,24] while doping C 8 BTBT through the partial charge transfer to form the charge-transfer complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation